An Unprecedented Revolution in Targeted Drug Delivery Using Photonics: Overcoming Global Challenges - A. Q. Noha (An Unprecedented Revolution in Targeted Drug Delivery Using Photonics: Overcoming Global Challenges, 2023)
Notwithstanding the endless efforts on targeted drug delivery, specially upon the arrisal of uncontrallable moratlity rates due to SARS-COV-2 and cancer, there has never been an FDA approved drug or a treatment approach. Therefore, this work was dedicated to find a new approach to not only treat but also to image the dynamics of SARS-COV-2. This work aimed at adding multiple aspects that constitute a significant need to science and the worldwide health experts. First, not only does it review the conventional treatment approaches such as chemical, herbal, genetic, stem-cell based or other therapies, but the review extends, for the first time, to include all possible external triggers that could interact with SARS-COV-2. Second, a generic treatment and imaging approach is then outlined, to expand the range of benefit to all researchers who aim at continuity of study in this field. Third, and importantly, the protocol is generic to be applicable to all targeted drug delivery applications, which is detailed through the explanation of the design objectives, requirements, and a guided, evidence-oriented development of the selected protocol, which will be significant to other targeted drug delivery applications such as cancer, with a manimial changes in the dose, and coating. Fourth, exhaustive reviews have been conducted on the chosen protocol involving electromagnetic interactions, which have not been applied, due to the non-biodegradibility of the gold or metal nanoparticles required to achieve a certain field enhancement. In the meanwhile, more than 1300 materials that have been theoretically or emperically studied to have a capability to target SARS-COV-2, have been reviewed for their capability to achieve the required electromagnetic interactions, but none of them could theoretically, at their best, provide the required interaction specifications. Moreover, and fifth, an exhaustive review for all field enhancement approaches have been reviewed in this work, as well, but none of them could be applicable in this case of concern, for detailed reasoning that has been provided in this work, too. Therefore, and sixth, a novel field enhancement approach has been designed. This approach was intended to help the entire world of drug delivery, since it is material independent, which helps with the replicability of this approach to other targeted drug delivery applications, even upon changing the targeting coating material. Furthermore, the approach is verified numerically and empirically. Seventh, not only does this work provide a novel field enhancement approach, but it sets up an unprecedented, detailed roadmap for field enhancement to facilitate and accelerate the entire world-wide research in this field. Eighth, this work applies all of the outlined protocol milestones theoretically and practically to verify it, which sets a pioneering gateway for the world of targeted drug delivery, using novel perspectives. Ninth, this work was considering the strictly limited technological capabilities in Egypt, which is helpful in the sense of simplicity and cost-efficiency, that suit other developing countries.